Neodymium-iron-boron magnet product with plating layer, electroplating method of neodymium-iron-boron magnet product and electronic product
By pickling and electroplating the neodymium iron boron magnets, adjusting their surface roughness and plating thickness, the problems of insufficient corrosion resistance and binding force of existing magnet coatings are solved, and thinner and stronger binding force are achieved. Adapt to the trend of miniaturization and improve the overall performance of magnets.
Patent Information
- Application Number
- CN202411740840.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Under the stricter corrosion resistance and bonding force testing requirements of existing neodymium iron boron magnet products, the corrosion resistance and bonding force of the galvanized layer are insufficient, and the thickness and uniformity of the coating are difficult to meet the needs of the trend of miniaturization.
An electroplating method is adopted, including pre-treatment of the NdFeB matrix, adjusting its surface roughness within the range of 0.2 to 0.35 μm, and then performing first electrogalvanized and second electrogalvanized nickel, by regulating the composition of the electroplating solution and process parameters to improve the binding force and corrosion resistance of the coating.
On the basis of thinner plating, the binding force between the plating and the neodymium iron boron matrix is achieved, the corrosion resistance and corrosion resistance of the magnet are enhanced, and the corrosion resistance of the magnet is adapted to the trend of miniaturization, and it is also shown in drop, salt spray and high temperature and high humidity tests. Excellent performance.
Smart Images

Figure CN119433646A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB, and in particular to a NdFeB magnet product with a coating, an electroplating method thereof, and an electronic product. Background Art
[0002] Common surface treatment methods for NdFeB include electrogalvanizing, electroplating nickel-copper-nickel, electrophoresis, phosphating, etc.
[0003] Products used in 3C electronic devices such as mobile phones, speakers, bracelets, tablets, headphones, etc. require the surface of the magnet to be an electroplated zinc layer (which has high requirements for the demagnetization and adhesiveness of the magnet). With the increase in the use environment of terminal products, especially small acoustic products, in recent years, the requirements for the corrosion resistance and bonding strength test quality of the products have increased. The original zinc-plated layer on the surface of the magnet can no longer meet its more stringent corrosion resistance requirements, and new research on the surface treatment of the magnet is needed.
[0004] In addition, as more application scenarios tend to develop towards miniaturization, higher requirements are placed on the thickness of the coating towards thinner and more uniform directions.
[0005] Therefore, these requirements for thinner, more uniform and stronger coatings pose new challenges to the surface treatment methods of NdFeB. Summary of the invention
[0006] To solve the above technical problems, the present invention provides a NdFeB magnet product with a coating, an electroplating method thereof and an electronic product, which can achieve a better bonding effect between the coating and the NdFeB substrate on the basis of obtaining a thinner coating, and has broad application prospects.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for electroplating NdFeB, the electroplating method comprising the following steps:
[0009] The NdFeB matrix is first pre-treated to obtain a pre-treated NdFeB matrix, wherein the pre-treatment includes pickling; the pre-treated NdFeB matrix is subjected to a first electroplating zinc in a first electroplating solution to obtain a first NdFeB magnet containing a zinc-plated layer; the first NdFeB magnet is subjected to a second electroplating zinc-nickel in a second electroplating solution to obtain a second NdFeB magnet containing a zinc-nickel layer; wherein the surface roughness Ra of the pre-treated NdFeB matrix is 0.2 to 0.35 μm; and the surface roughness Ra of the first NdFeB is 0.3 to 0.45 μm.
[0010] It is worth noting that conventional technical thinking in this field believes that the higher the pre-treatment surface roughness of the NdFeB substrate, the more conducive it is to the improvement of the bonding strength between the substrate and the coating. However, the researchers of this application found that when the surface of the NdFeB substrate is pre-treated by pickling with an acidic solution, if the surface roughness of the NdFeB substrate is too high, it will affect the state of the near-surface area of the NdFeB substrate, so that after subsequent electroplating, the near-surface area of the NdFeB substrate is prone to cracks, which will reduce the bonding strength between the substrate and the coating (especially not conducive to the drop test). Therefore, after the NdFeB substrate is pre-treated, its surface roughness needs to be controlled within a reasonable range, so that the bonding strength of the coating is improved, and at the same time, the state of cracks in the near-surface area of the substrate can be suppressed. However, after comprehensively studying multiple factors such as the bonding strength of the coating, the roughness of the substrate, and the state of the near-surface area of the substrate, the present applicant adjusted the surface roughness of the NdFeB substrate after pre-treatment to the range of Ra=0.2~0.35μm, in order to maximize the protection of the state of the near-surface area of the substrate, reduce the occurrence of NdFeB substrate after electroplating, and make the final drop test present better results.
[0011] Furthermore, on the basis of adjusting the surface roughness of the NdFeB substrate to Ra=0.2~0.35μm, in order to improve the bonding strength of the zinc-nickel layer, after the first electro-galvanizing, the surface roughness of the zinc-plated layer is adjusted to within the range of Ra of 0.3~0.45μm. The roughness of the zinc-plated layer is improved compared with the prior art. When the substrate roughness is low, the roughness is greatly increased by the zinc-plated layer, which can improve the electroplating basis of the final coating, that is, the anti-corrosion effect of the electro-galvanized nickel layer is better.
[0012] Specifically, the surface roughness Ra of the NdFeB matrix after pre-treatment is 0.2~0.35μm, for example, it can be 0.2μm, 0.22μm, 0.24μm, 0.25μm, 0.27μm, 0.29μm, 0.3μm, 0.32μm, 0.34μm or 0.35μm, etc.; the surface roughness Ra of the first NdFeB is 0.3~0.45μm, for example, it can be 0.3μm, 0.32μm, 0.34μm, 0.35μm, 0.37μm, 0.39μm, 0.4μm, 0.42μm, 0.44μm or 0.45μm, etc.
[0013] Preferably, the first electroplating solution contains 150-240 g / L zinc sulfate, for example, it can be 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L or 240 g / L, etc., preferably 150-230 g / L.
[0014] It is worth noting that, since the surface roughness of the NdFeB substrate is adjusted to Ra=0.2-0.35 μm, it is difficult to achieve the coating bonding strength requirements using the conventional first electroplating solution (i.e., electrogalvanizing solution). Therefore, the present application has made more precise adjustments to the electrogalvanizing solution, specifically including: 1) The electrogalvanizing solution includes a relatively low content of 150-240 g / L zinc sulfate. The reduction in the concentration of zinc sulfate can protect the surface state of the substrate during the electroplating process to the greatest extent, making it difficult for cracks to expand. 2) The electrogalvanizing solution does not include brighteners. Brighteners will decompose during the electroplating process, and the organic matter produced after decomposition is not easy to remove. During the electroplating process, the decomposed organic matter gradually accumulates, and the increased concentration increases the brittleness of the zinc coating, thereby deteriorating the bonding strength of the zinc coating.
[0015] Optionally, the first electroplating solution contains sodium sulfate, and the concentration of sodium sulfate in the first electroplating solution is 100-200 g / L, for example, it can be 100 g / L, 112 g / L, 123 g / L, 134 g / L, 145 g / L, 156 g / L, 167 g / L, 178 g / L, 189 g / L or 200 g / L, etc.
[0016] Furthermore, after controlling the surface state of the NdFeB substrate, due to the low roughness of the surface of the NdFeB substrate, the plating rate of the zinc coating is affected to a certain extent. In order to control the roughness value of the zinc coating within the above range and prevent the near-surface area of the substrate from being further affected during the electrogalvanizing process, the present invention further adds 100 to 200 g / L of sodium sulfate to the first electroplating solution. When the sodium sulfate is within the above range, the electrogalvanized layer can achieve a roughness of Ra = 0.3 to 0.45 μm at a relatively thin thickness of less than 7 μm. The roughness of the zinc coating is improved compared with the prior art. When the roughness of the NdFeB substrate is low, the roughness is greatly improved through the first electrogalvanizing, which can improve the electroplating basis of the final zinc-nickel layer and enable the zinc-nickel layer to have a better anti-corrosion effect.
[0017] In the present invention, sodium sulfate plays the role of a conductive salt, and can improve the conductivity of the first electroplating solution and the current efficiency of the first electroplating solution.
[0018] Optionally, the first electroplating solution contains boric acid, and the concentration of boric acid in the first electroplating solution is 10-40 g / L, for example, it can be 10 g / L, 14 g / L, 17 g / L, 20 g / L, 24 g / L, 27 g / L, 30 g / L, 34 g / L, 37 g / L or 40 g / L.
[0019] Optionally, the pH value of the first electroplating solution is 3.0-5.0, for example, 3.0, 3.3, 3.5, 3.7, 3.9, 4.2, 4.4, 4.6, 4.8 or 5.0.
[0020] Preferably, the temperature of the first electroplating solution during the first electrogalvanizing process is 20-35°C, for example, 20°C, 22°C, 24°C, 25°C, 27°C, 29°C, 30°C, 32°C, 34°C or 35°C.
[0021] Optionally, the current density during the first electrogalvanizing process is 0.1-2 A / dm 2 , for example, it can be 0.1A / dm 2 , 0.4A / dm 2 , 0.6A / dm 2 , 0.8A / dm 2 , 1A / dm 2 , 1.2A / dm 2 , 1.4A / dm 2 , 1.6A / dm 2 , 1.8A / dm 2 or 2A / dm 2 wait.
[0022] Optionally, the thickness of the zinc-plated layer is 0.1 to 7 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1.2 μm, 1.9 μm, 2.5 μm, 3.2 μm, 3.9 μm, 4.5 μm, 5.2 μm, 5.9 μm, 6.5 μm, 6.8 μm or 7.0 μm.
[0023] Optionally, the first electrogalvanizing includes at least one sub-electroplating process. The number of sub-electroplating processes in the present invention can be greater than one, as long as the total thickness satisfies the thickness of the zinc-plated layer of 0.1 to 7.0 μm and the roughness is Ra=0.3 to 0.45 μm.
[0024] Preferably, between the first electro-galvanizing and the second electro-galvanizing of zinc and nickel, the electro-plating method further comprises: activating the first NdFeB.
[0025] Optionally, the activation includes: placing the first NdFeB magnet in an activation solution for cleaning.
[0026] Optionally, the activation solution used in the activation is a hydrochloric acid solution.
[0027] Optionally, the volume concentration of the hydrochloric acid solution in the activation is 0.2-0.6%, for example, it can be 0.2%, 0.25%, 0.29%, 0.34%, 0.38%, 0.43%, 0.47%, 0.52%, 0.56% or 0.6%, etc.
[0028] Optionally, the activated cleaning time is 5 to 15 s, for example, it may be 5 s, 7 s, 8 s, 9 s, 10 s, 11 s, 12 s, 13 s, 14 s or 15 s.
[0029] Preferably, the second electroplating solution contains 10-30 g / L zinc chloride, for example, it can be 10 g / L, 13 g / L, 15 g / L, 17 g / L, 19 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L.
[0030] Optionally, the second electroplating solution contains 200-260 g / L potassium chloride, for example, it can be 200 g / L, 207 g / L, 214 g / L, 220 g / L, 227 g / L, 234 g / L, 240 g / L, 247 g / L, 254 g / L or 260 g / L, etc., preferably 230-260 g / L.
[0031] Optionally, the second electroplating solution contains 10-40 g / L nickel chloride, for example, it may be 10 g / L, 14 g / L, 17 g / L, 20 g / L, 24 g / L, 27 g / L, 30 g / L, 34 g / L, 37 g / L or 40 g / L.
[0032] Optionally, the mass ratio of zinc chloride to nickel chloride in the second electroplating solution is (2-4):1, for example, it can be 2:1, 2.3:1, 2.5:1, 2.7:1, 2.9:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1 or 4:1, etc.
[0033] It is worth noting that in the present invention, the zinc-plated layer is in close contact with the NdFeB substrate, and the bonding state of the zinc-plated layer and the NdFeB substrate has a great influence on the effect of the drop test; and the zinc-nickel layer is very critical for corrosion protection. In the second electroplating zinc-nickel treatment process, in order to make the zinc-plated nickel layer stably and evenly plated on the basis of the zinc-plated layer, and finally improve the corrosion resistance of the zinc-plated nickel layer, improve the consistency of the coating and the degree of stable control during the electroplating process, it can be controlled from two aspects. On the one hand, the solution composition, in the second electroplating solution, the concentration of potassium chloride is controlled to be 200-260g / L, and by increasing the amount of potassium chloride added, it can better complex the zinc ions in the solution. In addition, 1-10ml / L of complexing agent is added at the same time to better complex the nickel ions in the solution. Finally, the mass ratio of zinc chloride to nickel chloride is controlled at 2:1-4:1, the brightness of the low current density area is improved, and the nickel content in the high and low current density areas is made more uniform, and the nickel content in the coating is controlled to be 0.1-20wt%, and a uniform plating effect is achieved.
[0034] Furthermore, from the perspective of stable control of the solution, it is preferred that during the zinc-nickel electroplating process, a complexing agent and a buffer are added to the plating solution at least once, and the volume ratio of the complexing agent and the buffer added each time to the volume ratio of pure water is 1:(2-5), for example, it can be 1:2, 1:2.5, 1:2.8, 1:3.0, 1:3.2, 1:3.3, 1:3.5, 1:3.8, 1:4.0, 1:4.5 or 1:5, etc., and the complexing agent and the buffer are added to the plating solution in proportion once every 1000 ampere hours.
[0035] Optionally, the second electroplating solution does not contain boric acid.
[0036] Optionally, the second electroplating solution further contains 1-10 ml / L of complexing agent, for example, it can be 1 ml / L, 2 ml / L, 3 ml / L, 4 ml / L, 5 ml / L, 6 ml / L, 7 ml / L, 8 ml / L, 9 ml / L or 10 ml / L, etc.
[0037] Optionally, the complexing agent includes 15-25% diethylenetriamine, 10-30% sodium benzoate and 2-6% p-toluenesulfonic acid in terms of mass percentage.
[0038] Specifically, 15-25% diethylenetriamine, for example, it can be 15%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25% etc.; 10-30% sodium benzoate, for example, it can be 10%, 13%, 15%, 17%, 19%, 22%, 24%, 26%, 28% or 30% etc.; and 2-6% p-toluenesulfonic acid, for example, it can be 2%, 2.5%, 2.9%, 3.4%, 3.8%, 4.3%, 4.7%, 5.2%, 5.6% or 6% etc.
[0039] The present invention adopts a complexing agent to improve the brightness of the low current density area, make the nickel content of the high and low current density areas more uniform, and reduce the burning of the high current density area.
[0040] Optionally, the second electroplating solution further contains 70-110 ml / L of a buffer, for example, 70 ml / L, 75 ml / L, 79 ml / L, 84 ml / L, 88 ml / L, 93 ml / L, 97 ml / L, 102 ml / L, 106 ml / L or 110 ml / L, etc. The addition of a buffer in the present invention can prevent the high current density area from burning.
[0041] Optionally, the buffer comprises potassium acetate at a concentration of 40-60wt%, for example, 40wt%, 43wt%, 45wt%, 47wt%, 49wt%, 52wt%, 54wt%, 56wt%, 58wt% or 60wt%, etc.
[0042] In the second zinc-nickel electroplating solution, the present invention adds an ultra-high content of buffer 226 (70-110 ml / L), and the buffer includes potassium acetate with a concentration of 40-60 wt%. By adding the buffer, the electroplating process in the high current density area (at the top angle of the magnet) can be accurately controlled, so that the overall electroplating process of the coating is more balanced, the extreme value of the edges and centers of the coating is reduced, and the final roughness is controllable, achieving the technical effect of Ra=0.2-0.35 μm. If the buffer content is low, the edges and corners of the product will appear black after electroplating, and the anti-corrosion performance will be greatly reduced.
[0043] Optionally, the second electroplating solution also contains a brightener, and the concentration of the brightener is 0.1-10 ml / L, for example, it can be 0.1 ml / L, 1.2 ml / L, 2.3 ml / L, 3.4 ml / L, 4.5 ml / L, 5.6 ml / L, 6.7 ml / L, 7.8 ml / L, 8.9 ml / L or 10 ml / L.
[0044] Optionally, the second electroplating solution also contains a wetting agent, and the concentration of the wetting agent is 1 to 20 ml / L, for example, it can be 1 ml / L, 4 ml / L, 6 ml / L, 8 ml / L, 10 ml / L, 12 ml / L, 14 ml / L, 16 ml / L, 18 ml / L or 20 ml / L.
[0045] The present invention has no special limitation on the wetting agent in the above process. Any wetting agent that can be used in electroplating solution and is well known to those skilled in the art can be used, and can also be adjusted according to the actual process.
[0046] Optionally, the second electroplating solution also contains a low-level enhancer, and the concentration of the low-level enhancer is 0.1-10 ml / L, for example, it can be 0.1 ml / L, 1.2 ml / L, 2.3 ml / L, 3.4 ml / L, 4.5 ml / L, 5.6 ml / L, 6.7 ml / L, 7.8 ml / L, 8.9 ml / L or 10 ml / L, etc.
[0047] The present invention has no special limitation on the low-level enhancer in the above process. Any low-level enhancer that can be used in electroplating solution and is well known to those skilled in the art can be used, and can also be adjusted according to the actual process.
[0048] Preferably, the temperature of the second electroplating zinc-nickel is 25°C to 36°C, for example, it can be 25°C, 27°C, 28°C, 29°C, 30°C, 32°C, 33°C, 34°C, 35°C or 36°C.
[0049] Optionally, the pH value of the second electroplating zinc-nickel is 5.0-5.7, for example, it can be 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6 or 5.7.
[0050] Optionally, the current density of the second zinc-nickel electroplating is 0.1-5A / dm 2 , for example, it can be 0.1A / dm 2 , 0.7A / dm 2 , 1.2A / dm 2 , 1.8A / dm 2 , 2.3A / dm 2 , 2.9A / dm 2 , 3.4A / dm 2 , 4A / dm 2 , 4.5A / dm 2 or 5A / dm 2 wait.
[0051] Optionally, the zinc-nickel plated layer has a thickness of 0.1 to 6 μm, for example, 0.1 μm, 0.8 μm, 1.5 μm, 2.1 μm, 2.8 μm, 3.4 μm, 4.1 μm, 4.7 μm, 5.4 μm or 6 μm.
[0052] Optionally, the nickel content in the zinc-plated nickel layer is 0.1-20wt%, for example, it can be 0.1wt%, 2.4wt%, 4.6wt%, 6.8wt%, 9wt%, 11.2wt%, 13.4wt%, 15.6wt%, 17.8wt% or 20wt%.
[0053] Optionally, the surface roughness of the zinc-nickel plated layer is Ra=0.2-0.35 μm, for example, it may be 0.2 μm, 0.22 μm, 0.24 μm, 0.25 μm, 0.27 μm, 0.29 μm, 0.3 μm, 0.32 μm, 0.34 μm or 0.35 μm, etc.
[0054] Preferably, the pre-treatment comprises: the NdFeB substrate is subjected to grinding and chamfering, pickling and ultrasonic cleaning in sequence.
[0055] Optionally, the grinding and chamfering includes: using a vibration grinding and chamfering machine and / or a centrifugal grinding and chamfering machine, using abrasives, removing burrs on the surface of the NdFeB substrate, and grinding the right angles at the corners into R angles.
[0056] Optionally, the electroplating method further comprises a degreasing process arranged between the grinding chamfering and the pickling.
[0057] Optionally, the degreasing process includes: using a metal cleaning agent to remove oil stains on the surface of the chamfered NdFeB substrate.
[0058] Optionally, the concentration of the cleaning agent in the metal cleaning agent is 2-6wt%, for example, it can be 2wt%, 2.5wt%, 2.9wt%, 3.4wt%, 3.8wt%, 4.3wt%, 4.7wt%, 5.2wt%, 5.6wt% or 6wt%, etc.
[0059] Optionally, the temperature of the oil removal process is 40-60°C, for example, 40°C, 43°C, 45°C, 47°C, 49°C, 52°C, 54°C, 56°C, 58°C or 60°C.
[0060] Optionally, the processing time of the oil removal process is 90 to 150 s, for example, it may be 90 s, 95 s, 105 s, 110 s, 115 s, 125 s, 130 s, 135 s, 140 s or 150 s.
[0061] Optionally, the pickling includes: using acid to remove the oxide layer on the surface of the NdFeB substrate. The oxide layer on the surface is removed to obtain a NdFeB substrate without an oxide layer and corrosion products.
[0062] Optionally, the pickling includes at least one sub-pickling, which can be divided into two pickling steps.
[0063] Optionally, the acid solution used for pickling is 1-4wt% nitric acid, for example, it can be 1wt%, 1.4wt%, 1.7wt%, 2wt%, 2.4wt%, 2.7wt%, 3wt%, 3.4wt%, 3.7wt% or 4wt%.
[0064] Optionally, the pretreatment further includes a pre-activation step provided after ultrasonic cleaning; the pre-activation step includes: cleaning the NdFeB substrate after ultrasonic cleaning using a pre-activation solution.
[0065] The present invention uses an ultrasonic cleaning machine to clean the surface of the NdFeB substrate after pickling to prevent poor bonding and impurities from being brought into the electroplating solution.
[0066] Optionally, the pre-activation solution includes an activator with a volume concentration of 5-12%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%.
[0067] Optionally, the cleaning time of the pre-activation step is 5 to 15 s, for example, it can be 5 s, 7 s, 8 s, 9 s, 10 s, 11 s, 12 s, 13 s, 14 s or 15 s.
[0068] Optionally, after the second electroplating of zinc-nickel, the electroplating method further comprises: sequentially subjecting the second NdFeB magnet to light exposure, passivation and drying to obtain a NdFeB magnet product with a coating.
[0069] Optionally, the light extraction includes: treating the second NdFeB with a HCl solution having a volume concentration of 0.1-0.6% to extract light, for example, it can be 0.1%, 0.2%, 0.3%, 0.3%, 0.4%, 0.4%, 0.5%, 0.5%, 0.6% or 0.6%, etc.
[0070] Optionally, the light emitting time is 5 to 45 seconds, for example, it may be 5 seconds, 10 seconds, 14 seconds, 19 seconds, 23 seconds, 28 seconds, 32 seconds, 37 seconds, 41 seconds or 45 seconds.
[0071] Optionally, the passivation agent includes a trivalent chromium passivation solution.
[0072] Optionally, the pH value of the trivalent chromium passivation solution is 4.0-4.5, for example, it can be 4.0, 4.1, 4.2, 4.3, 4.4 or 4.5.
[0073] Optionally, the concentration of chromium in the trivalent chromium passivation solution is 1.5-2.5 g / L, for example, it can be 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2.0 g / L, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L or 2.5 g / L.
[0074] Optionally, the passivation temperature is 20-30°C, for example, 20°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C.
[0075] Optionally, the passivation time is 40 to 90 seconds, for example, 40 seconds, 46 seconds, 52 seconds, 57 seconds, 63 seconds, 68 seconds, 74 seconds, 79 seconds, 85 seconds or 90 seconds.
[0076] As a preferred technical solution of the present invention, the electroplating method comprises the following steps:
[0077] (1) Using a vibrating chamfering machine and / or a centrifugal chamfering machine, use abrasives to remove burrs on the surface of the NdFeB substrate and grind the right angles at the corners into R angles; then use 2 to 6 wt% metal cleaning agent to remove oil stains on the chamfered NdFeB substrate surface at 40 to 60°C for 90 to 150 seconds.
[0078] Then, 1-4wt% nitric acid is used to remove the oxide layer on the surface of the NdFeB substrate to obtain a NdFeB substrate without an oxide layer and corrosion products; an ultrasonic cleaner is used to clean the surface of the NdFeB substrate after pickling, and then the NdFeB substrate after ultrasonic cleaning is cleaned with an activator with a volume concentration of 5-12% for 5-15s to obtain a pre-treated NdFeB substrate.
[0079] (2) After the pretreatment, the NdFeB substrate is electroplated in a first electroplating solution at a current density of 0.1 to 2 A / dm 2 The first electroplating zinc is carried out, the pH of the first electroplating solution is 3.0-5.0, and the temperature is 20-35° C., to obtain a first NdFeB magnet containing a zinc-plated layer.
[0080] The first electroplating solution comprises 150-240 g / L zinc sulfate, 100-200 g / L sodium sulfate, and 10-40 g / L boric acid.
[0081] (3) The first NdFeB magnet is placed in a 0.2-0.6% hydrochloric acid solution for cleaning for 5-15 seconds to obtain an activated first NdFeB magnet.
[0082] (4) The zinc-containing NdFeB layer is electroplated in a second electroplating solution at a current density of 0.1 to 5 A / dm 2 A second zinc-nickel electroplating is performed, the temperature of the second zinc-nickel electroplating is 25° C. to 36° C., the pH value of the second zinc-nickel electroplating is 5.0 to 5.7, and a second NdFeB magnet containing a zinc-nickel plating layer is obtained.
[0083] Among them, the composition of the second electroplating solution includes 10-30g / L zinc chloride, 200-260g / L potassium chloride, 10-40g / L nickel chloride, 1-10ml / L complexing agent (according to the mass percentage, the complexing agent includes 15-25% diethylenetriamine, 10-30% sodium benzoate and 2-6% p-toluenesulfonic acid), 70-110ml / L buffer (potassium acetate with a concentration of 40-60wt%), 0.1-10ml / L brightener, 1-20ml / L wetting agent, and 0.1-10ml / L low-position strengthener.
[0084] (5) The second NdFeB is treated with a 0.1-0.6% by volume HCl solution to emit light for 5-45 seconds, and then the second NdFeB is passivated for 40-90 seconds at 20-30°C with a trivalent chromium passivation solution having a pH value of 4.0-4.5 and a chromium concentration of 1.5-2.5 g / L, and finally blow-dried to obtain a NdFeB magnet product with a coating.
[0085] The preparation method of the NdFeB matrix of the present invention comprises:
[0086] 1) The alloy quick-setting sheet is made by using the quick-setting process.
[0087] 2) The quick-setting sheet is hydrogen-crushed and jet-milled with additives to obtain alloy powder, and the average particle size D50 of the alloy powder is 2-5 μm.
[0088] 3) The alloy powder obtained in step 2) is pressed and molded under magnetic field orientation, and the magnetic field strength is 1.8-2.5T to obtain a compact.
[0089] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to obtain a blank.
[0090] The sintering process is as follows: the sintering temperature is 1030-1120° C., and the sintering time is 1-10 hours, preferably 6-10 hours.
[0091] The aging process is as follows: the first-level aging temperature is 870-1000°C, the holding time is 0.5-6h, the second-level aging temperature is 450-700°C, and the holding time is 1-10h.
[0092] 5) The blank is machined to obtain a NdFeB matrix of corresponding size.
[0093] In a second aspect, the present invention provides a NdFeB magnet product with a coating, wherein the NdFeB magnet product is produced by the NdFeB electroplating method described in the first aspect.
[0094] Preferably, the NdFeB magnet product comprises a NdFeB matrix and a zinc-plated layer and a zinc-nickel-plated layer sequentially arranged on the surface of the NdFeB matrix.
[0095] Optionally, the thickness of the zinc-plated layer is 0.5-6.5 μm, for example, 0.5 μm, 1.2 μm, 1.9 μm, 2.5 μm, 3.2 μm, 3.9 μm, 4.5 μm, 5.2 μm, 5.9 μm or 6.5 μm.
[0096] Optionally, the zinc-nickel plated layer has a thickness of 0.1 to 6 μm, for example, 0.1 μm, 0.8 μm, 1.5 μm, 2.1 μm, 2.8 μm, 3.4 μm, 4.1 μm, 4.7 μm, 5.4 μm or 6 μm.
[0097] Optionally, the nickel content in the zinc-plated nickel layer is 0.1-20wt%, for example, it can be 0.1wt%, 2.4wt%, 4.6wt%, 6.8wt%, 9wt%, 11.2wt%, 13.4wt%, 15.6wt%, 17.8wt% or 20wt%.
[0098] Optionally, the total length of cracks in the near-surface zone of the NdFeB matrix is less than or equal to 130 μm, for example, it can be 10 μm, 12 μm, 13 μm, 15 μm, 20 μm, 22 μm, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm or 130 μm, etc.
[0099] The near-surface region described in the present invention refers to a region with a depth of 20 um from the surface of the NdFeB matrix to the inside of the NdFeB matrix.
[0100] Optionally, the composition of the NdFeB matrix includes 28-32wt% of R element, 0.85-1.05wt% of B element, 0-3wt% of M element excluding 0, and the balance T; wherein R represents a rare earth element, selected from Nd and at least one of the following rare earth elements: Pr, La, Ce, Gd, Dy, Tb and Ho; M is selected from any one or a combination of at least two of Cu, Ga, Zr, Ti, Nb, Al, Zn, Ag or W. T includes Fe and / or Co and other impurity elements, wherein Fe accounts for more than 97wt% of the total amount of T.
[0101] Specifically, 28-32wt% of the R element may be, for example, 28wt%, 28.5wt%, 28.9wt%, 29.4wt%, 29.8wt%, 30.3wt%, 30.7wt%, 31.2wt%, 31.6wt% or 32wt% or the like; 0.85-1.05wt% of the B element may be, for example, 0.85wt%, 0.88wt%, 0.9wt%, 0.92wt%, 0.94wt%, 0.97wt%, 0.99wt%, 1.01wt%, 1.03wt% or 1.05wt% or the like; 0-3wt% of the M element may be, for example, 0.1wt%, 0.4wt%, 0.7wt%, 1wt%, 1.4wt%, 1.7wt%, 2wt%, 2.4wt%, 2.7wt% or 3wt% or the like.
[0102] The present invention has no special limitation on the activator in the above process. Any activator known to those skilled in the art for activating the NdFeB matrix can be used. The activator can also be adjusted according to the actual process, for example, it can be dilute sulfuric acid, dilute hydrochloric acid, etc.
[0103] In a third aspect, the present invention provides an electronic product, comprising the coated NdFeB magnet product according to the second aspect.
[0104] The electronic product provided in the third aspect of the present invention comprises the NdFeB magnet product with coating provided in the second aspect, and thus has better corrosion resistance and drop resistance.
[0105] Compared with the prior art, the present invention has at least the following beneficial effects:
[0106] (1) The NdFeB electroplating method provided by the present invention can obtain a NdFeB magnet product with excellent corrosion resistance on the basis of a thinner coating. Specifically, the NdFeB magnet product with a coating prepared by the present invention can pass a load-bearing drop test of more than 50 times, preferably more than 60 times; and a salt spray resistance test of more than 100 hours, preferably more than 120 hours, and a high temperature and high humidity resistance test of more than 450 hours, preferably more than 504 hours;
[0107] (2) The thickness of the zinc-plated layer and the zinc-nickel-plated layer of the NdFeB magnet product obtained by the NdFeB electroplating method provided by the present invention is significantly reduced, which adapts to the trend of miniaturization of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0108] Figure 1 This is an electron microscope image of the NdFeB magnet product with coating provided in Example 1 of the present invention.
[0109] Figure 2 This is an electron microscope image of the NdFeB magnet product with coating provided in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0110] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0111] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0112] For the convenience of comparison, the preparation method of the NdFeB matrix provided in the following examples and comparative examples includes the following steps:
[0113] 1) The alloy quick-setting sheet is made by using the quick-setting process.
[0114] 2) The quick-setting sheet is hydrogen-crushed and jet-milled with additives to obtain alloy powder, and the average particle size D50 of the alloy powder is 3.5 μm.
[0115] 3) The alloy powder obtained in step 2) is pressed and molded under magnetic field orientation with a magnetic field strength of 2.0 T to obtain a compact.
[0116] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to obtain a blank.
[0117] The sintering process is as follows: the sintering temperature is 1100° C. and the sintering time is 5 hours, preferably 6 to 10 hours.
[0118] The aging process is as follows: the first-stage aging temperature is 900°C, the holding time is 6h, the second-stage aging temperature is 500°C, and the holding time is 8h.
[0119] 5) The blank is machined to obtain a NdFeB matrix of corresponding size.
[0120] Example 1
[0121] This embodiment provides an electroplating method for NdFeB, the electroplating method comprising the following steps:
[0122] The composition of the NdFeB matrix in this embodiment is (PrNd) 29.5 Co1B 0.9 Cu 0.1 Ga 0.3 Al 0.1 Fe 余 , the subscript indicates the mass percentage.
[0123] (1) A vibrating chamfering machine is used to remove burrs on the surface of the NdFeB substrate using abrasives, and the right angles at the corners are ground into R angles; then a 3.5wt% metal cleaning agent (specifically 3M TM Citrus-Based Cleaner / Degreaser7100) was used to remove oil stains on the surface of the chamfered NdFeB substrate at 50°C for 120s.
[0124] Then, 2.5wt% nitric acid was used twice to remove the oxide layer on the surface of the NdFeB substrate to obtain a NdFeB substrate without an oxide layer and corrosion products; an ultrasonic cleaner was used to clean the surface of the NdFeB substrate after pickling, and then the NdFeB substrate after ultrasonic cleaning was cleaned with an activator (Tween 20) with a volume concentration of 8% for 10s to obtain a pre-treated NdFeB substrate, and the surface roughness Ra of the pre-treated NdFeB substrate was 0.2μm.
[0125] (2) After the pretreatment, the NdFeB substrate is electroplated in a first electroplating solution at a current density of 1.0 A / dm 2 The first electroplating zinc is performed, the pH of the first electroplating solution is 4.0, and the temperature is 30° C., to obtain a first NdFeB magnet containing a zinc-plated layer.
[0126] The first electroplating solution comprises 200 g / L zinc sulfate, 150 g / L sodium sulfate and 20 g / L boric acid.
[0127] (3) The first NdFeB magnet is placed in a 0.5% hydrochloric acid solution for cleaning for 10 seconds to obtain an activated first NdFeB magnet.
[0128] (4) Plating the first NdFeB magnet through a second electroplating solution at a current density of 3.5 A / dm 2The second electroplating of zinc-nickel is performed, the temperature of the second electroplating of zinc-nickel is 30° C., the pH value of the second electroplating of zinc-nickel is 5.2, and a second NdFeB magnet containing a zinc-nickel layer is obtained. From the stable control of the second electroplating solution, during the second electroplating of zinc-nickel, a complexing agent and a buffer are added to the electroplating solution at least once, the volume ratio of the complexing agent and the buffer added each time to the volume ratio of pure water is 1:2.5, and the complexing agent and the buffer are added to the electroplating solution in proportion every 1000 ampere hours.
[0129] Among them, the composition of the second electroplating solution includes 25g / L zinc chloride, 250g / L potassium chloride, 30g / L nickel chloride, 5ml / L complexing agent (according to the mass percentage, the complexing agent includes 20% diethylenetriamine, 25% sodium benzoate and 3.5% p-toluenesulfonic acid), and 100ml / L buffer (potassium acetate with a concentration of 50wt%).
[0130] (5) The second NdFeB magnet is treated with a 0.5% by volume HCl solution to emit light for 35 seconds, and then the second NdFeB is passivated for 50 seconds at 25°C using a trivalent chromium passivation solution with a pH value of 4.2 and a chromium concentration of 2 g / L, and finally blow-dried to obtain a NdFeB magnet product with a coating.
[0131] Example 2
[0132] This embodiment provides an electroplating method for NdFeB, the electroplating method comprising the following steps:
[0133] The composition of the NdFeB matrix in this embodiment is the same as that in Embodiment 1.
[0134] (1) A centrifugal grinding and chamfering machine is used to remove burrs on the surface of the NdFeB substrate using abrasives, and the right angles at the corners are ground into R angles; then a 2wt% metal cleaning agent (specifically 3M TM Citrus-Based Cleaner / Degreaser7100) was used to remove oil stains on the surface of the chamfered NdFeB substrate at 40°C for 150s.
[0135] Then, 3wt% nitric acid is used twice to remove the oxide layer on the surface of the NdFeB substrate to obtain a NdFeB substrate without an oxide layer and corrosion products; an ultrasonic cleaner is used to clean the surface of the NdFeB substrate after pickling, and then the NdFeB substrate after ultrasonic cleaning is cleaned with an activator (Tween 80) with a volume concentration of 12% for 10 seconds to obtain a pre-treated NdFeB substrate. The surface roughness Ra of the pre-treated NdFeB substrate is 0.35μm. (2) The pre-treated NdFeB substrate is electroplated in a first electroplating solution at a current density of 2.0A / dm 2The first electroplating zinc is performed, the pH of the first electroplating solution is 3.0, and the temperature is 35° C., to obtain a first NdFeB magnet containing a zinc-plated layer.
[0136] The first electroplating solution comprises 240 g / L zinc sulfate, 100 g / L sodium sulfate, and 10 g / L boric acid.
[0137] (3) The first NdFeB magnet is placed in a 0.6% hydrochloric acid solution for cleaning for 15 seconds to obtain an activated first NdFeB magnet.
[0138] (4) The first NdFeB magnet is electroplated with a second electroplating solution at a current density of 0.1 A / dm 2 The second electroplating of zinc-nickel is performed, the temperature of the second electroplating of zinc-nickel is 25° C., the pH value of the second electroplating of zinc-nickel is 5.7, and a second NdFeB magnet containing a zinc-nickel layer is obtained. From the stable control of the second electroplating solution, during the second electroplating of zinc-nickel, a complexing agent and a buffer are added to the electroplating solution at least once, the volume ratio of the complexing agent and the buffer added each time to the volume ratio of pure water is 1:5, and the complexing agent and the buffer are added to the electroplating solution in proportion once every 1000 ampere hours.
[0139] Among them, the composition of the second electroplating solution includes 10g / L zinc chloride, 260g / L potassium chloride, 10g / L nickel chloride, 10ml / L complexing agent (according to the mass percentage, the complexing agent includes 15% diethylenetriamine, 30% sodium benzoate and 6% p-toluenesulfonic acid), and 110ml / L buffer (potassium acetate with a concentration of 40wt%).
[0140] (5) The second NdFeB magnet is treated with a 0.1% by volume HCl solution to emit light for 45 seconds, and then the second NdFeB is passivated for 40 seconds at 30°C using a trivalent chromium passivation solution with a pH value of 4.5 and a chromium concentration of 2 g / L, and finally blow-dried to obtain a NdFeB magnet product with a coating.
[0141] Example 3
[0142] This embodiment provides an electroplating method for NdFeB. The electroplating method is the same as that of Embodiment 1 except that the first electroplating solution contains 260 g / L zinc sulfate, and thus will not be described in detail herein.
[0143] Example 4
[0144] This embodiment provides an electroplating method for NdFeB. The electroplating method is the same as that of Embodiment 1 except that the first electroplating solution contains 5 ml / L of brightener (specifically, the brightener is Parker Ionics 7-36), and will not be described in detail here.
[0145] Example 5
[0146] This embodiment provides an electroplating method for NdFeB. The electroplating method is the same as that of Embodiment 1 except that the second electroplating solution contains 150 g / L potassium chloride, and thus will not be described in detail herein.
[0147] Example 6
[0148] This embodiment provides an electroplating method for NdFeB. The electroplating method is the same as that of Embodiment 1 except that no buffer is added to the second electroplating solution, and thus will not be described in detail herein.
[0149] Comparative Example 1
[0150] This comparative example provides an electroplating method for NdFeB. The electroplating method is the same as Example 1 except that the surface roughness Ra of the NdFeB substrate after pre-treatment is 0.5 μm, and the details will not be repeated here.
[0151] Comparative Example 2
[0152] This comparative example provides an electroplating method for NdFeB. The electroplating method is the same as that of Example 1 except that the surface roughness Ra of the first NdFeB magnet is 0.25 μm, and will not be described in detail here.
[0153] Test Method
[0154] Drop test: Glue the coated NdFeB magnet product to the tooling, and place the glued sample in the air to dry naturally for 2 hours. Load the tooling with a weight of 1.2 kg, and then let the NdFeB magnet glued to the tooling fall freely from 1.6 meters to check whether the coating on the surface of the NdFeB magnet product is intact; the zinc coating on the surface of the NdFeB magnet product prepared in each embodiment is tested and observed to be detached from the substrate (the magnet is allowed to detach from the tooling, and the coating does not peel off or peel). If it does not peel off or peel off, it means that the coating bonding strength is qualified, and the number of weight-bearing drops that can be tolerated is calculated.
[0155] Salt spray test: neutral salt spray test, in which salt water containing 5% sodium chloride and a pH value of 6.5 to 7.2 is sprayed in the test chamber through a spray device, and the test piece is placed in the test chamber. The test chamber temperature is 35°C.
[0156] High temperature and high humidity test: The test piece is placed in a temperature of 60°C and a relative humidity of 90% for high temperature and high humidity test.
[0157] Taking Example 1 and Comparative Example 1 as examples, the electron microscope images of the NdFeB magnet products with coatings finally obtained are as follows: Figure 1 and Figure 2 As shown, from Figures 1-2 It can be seen that a large number of long cracks are generated in the near-surface area of the substrate of the NdFeB magnet product with coating obtained in Comparative Example 1, while Figure 1 The crack is significantly reduced and its length is shortened.
[0158] The test results of the above embodiments and comparative examples are shown in Table 1.
[0159] Table 1
[0160]
[0161] From Table 1 we can see that:
[0162] (1) It can be seen from Examples 1 to 2 that the electroplating method of NdFeB provided by the present invention has the advantages of thin coating, good bonding with the NdFeB matrix, and excellent corrosion resistance. The NdFeB magnet product with coating can be dropped with a load for more than 90 times, can withstand salt spray for more than 120 hours, can withstand high temperature and high humidity for more than 504 hours, and the total length of cracks in the near-surface area is less than or equal to 30 μm, which can adapt to the trend of miniaturization of application scenarios.
[0163] (2) Combining Example 1 and Example 3, it can be seen that the first electroplating solution in Example 1 contains 200 g / L zinc sulfate. Compared with the use of 260 g / L zinc sulfate in Example 3, the salt spray resistance time of the final NdFeB magnet product with a coating in Example 1 is 120 h, and the high temperature and high humidity resistance time is 504 h, while the salt spray resistance time of the final NdFeB magnet product with a coating in Example 3 is only 100 h, and the high temperature and high humidity resistance time is 450 h, and the number of load-bearing drops is only 60 times. This shows that the present invention can further improve the bonding strength and corrosion resistance of the zinc-nickel layer by preferably using a suitable concentration of zinc sulfate in the first electroplating solution;
[0164] (3) It can be seen from Example 1 and Example 4 that no brightener is added in Example 1. Compared with Example 4 in which a brightener is added, the surface roughness of the zinc-plated layer of the first NdFeB magnet in Example 1 is 0.32 μm, and the salt spray resistance time of the final NdFeB magnet product with a coating is 120 h, and the high temperature and high humidity resistance time is 504 h. However, the surface roughness of the zinc-plated layer of the first NdFeB magnet in Example 4 is 0.30 μm, and the salt spray resistance time of the final NdFeB magnet product with a coating is only 100 h, and the number of load-bearing drops is only 50 times. This shows that the present invention can further improve the roughness of the zinc-plated layer in the first NdFeB magnet by preferably not adding a brightener to the first electroplating solution, thereby improving the bonding strength and anti-corrosion performance of the zinc-nickel layer;
[0165] (4) It can be seen from Example 1 and Example 5 that the second electroplating solution in Example 1 contains 250 g / L potassium chloride. Compared with the 150 g / L potassium chloride in Example 5, the potassium chloride content in Example 5 is relatively low, and it is not easy to complex zinc ions, resulting in uneven plating. The number of load-bearing drops is only 50 times. This shows that the present invention can improve the corrosion resistance and drop resistance by preferably using a suitable concentration of potassium chloride in the second electroplating solution;
[0166] (5) In Example 6, no buffer was added, resulting in uncontrollable roughness, reduced anti-corrosion performance, and the number of load-bearing drops decreased to 50 times;
[0167] (6) In comparative example 1, the surface roughness Ra of the NdFeB substrate after pretreatment is 0.5 μm, which is too rough. The total length of cracks in the near-surface area is as high as 224 μm, and the number of load-bearing drops is only 20 times. The surface roughness Ra of the first NdFeB magnet in comparative example 2 is 0.25 μm, which leads to a significant decrease in the bonding strength of the coating, and the salt spray resistance time is only 48 h, and the high temperature and high humidity resistance is only 72 h. The corrosion resistance is not as good as that of Example 1. This shows that the present invention can obtain a NdFeB magnet product with a thin coating, excellent bonding strength and good corrosion resistance by selecting a NdFeB substrate with a specific roughness and combining it with a specific electroplating method, and has broad application prospects.
[0168] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for electroplating a neodymium iron boron magnet, characterized in that: The electroplating method comprises the following steps: The NdFeB matrix is first pre-treated to obtain a pre-treated NdFeB matrix, wherein the pre-treatment includes pickling; The pre-treated NdFeB substrate is subjected to a first electroplating zinc treatment in a first electroplating solution to obtain a first NdFeB magnet containing a zinc-plated layer; The first NdFeB magnet is subjected to a second electroplating of zinc and nickel in a second electroplating solution to obtain a second NdFeB magnet containing a zinc and nickel layer; Wherein, the surface roughness Ra of the NdFeB substrate after the pre-treatment is 0.2-0.35 μm; The surface roughness Ra of the first NdFeB magnet is 0.3-0.45 μm.
2. The electroplating method according to claim 1, characterized in that: The first electroplating solution contains 150-240 g / L zinc sulfate; And / or, the first electroplating solution contains sodium sulfate, and the concentration of sodium sulfate in the first electroplating solution is 100-200 g / L; And / or, the pH value of the first electroplating solution is 3.0-5.
0.
3. The electroplating method according to claim 1 or 2, characterized in that: During the first electroplating zinc process, the temperature of the first electroplating solution is 20-35° C.; And / or, the current density during the first electrogalvanizing process is 0.1-2A / dm 2 ; And / or, the thickness of the zinc coating is 0.1 to 7 μm; And / or, the first electrogalvanizing includes at least one sub-electroplating process.
4. The electroplating method according to claim 1, characterized in that: The second electroplating solution contains 10-30 g / L zinc chloride; and / or, the second electroplating solution contains 200-260 g / L potassium chloride; and / or, the second electroplating solution contains 10-40 g / L nickel chloride; The mass ratio of zinc chloride to nickel chloride in the second electroplating solution is (2-4):1; And / or, the second electroplating solution does not contain boric acid.
5. The electroplating method according to any one of claims 1 to 4, characterized in that: The second electroplating solution also contains 1 to 10 ml / L of a complexing agent; According to the mass percentage, the complexing agent includes 15-25% diethylenetriamine, 10-30% sodium benzoate and 2-6% p-toluenesulfonic acid; And / or, the second electroplating solution further contains 70-110 ml / L of a buffer; the buffer comprises potassium acetate with a concentration of 40-60 wt%.
6. The electroplating method according to any one of claims 1 to 5, characterized in that: During the second electroplating of zinc and nickel, the temperature of the second electroplating solution is 25° C. to 36° C.; And / or, the pH value of the second electroplating zinc-nickel is 5.0-5.7; And / or, the current density of the second electroplating zinc nickel is 0.1-5A / dm 2 ; And / or, the zinc-nickel plating layer has a thickness of 0.1 to 6 μm; And / or, the nickel content in the zinc-nickel plating layer is 0.1 to 20 wt %; And / or, the surface roughness of the zinc-nickel plating layer is Ra=0.2-0.35 μm.
7. The electroplating method according to any one of claims 1 to 6, characterized in that: The pre-treatment comprises: the NdFeB substrate is subjected to grinding and chamfering, pickling and ultrasonic cleaning in sequence; The electroplating method further comprises a degreasing process arranged between grinding and chamfering and pickling; And / or, the pre-treatment further comprises a pre-activation step arranged after ultrasonic cleaning; the pre-activation step comprises: cleaning the NdFeB substrate after ultrasonic cleaning with a pre-activation solution; And / or, after the second electroplating of zinc-nickel, the electroplating method further comprises: the second NdFeB magnet is sequentially subjected to light exposure, passivation and drying to obtain a NdFeB magnet product with a coating.
8. A coated NdFeB magnet product, characterized in that: The NdFeB magnet product is produced by the electroplating method for NdFeB magnets as described in any one of claims 1 to 7.
9. The NdFeB magnet product according to claim 8, characterized in that: The NdFeB magnet product comprises a NdFeB matrix and a zinc-plated layer and a zinc-nickel-plated layer sequentially arranged on the surface of the NdFeB matrix; And / or, the thickness of the zinc coating is 0.5 to 6.5 μm; And / or, the zinc-nickel plating layer has a thickness of 0.1 to 6 μm; And / or, the nickel content in the zinc-nickel plating layer is 0.1 to 20 wt %; And / or, the total length of cracks in the near-surface region of the NdFeB matrix is less than or equal to 130 μm.
10. An electronic product, characterized in that: The electronic product comprises the coated NdFeB magnet product according to claim 8 or 9.
Citation Information
Patent Citations
High corrosion resistance zinc-nickel alloy electroplating additive with weak acidity to neutrality and electroplating liquid
CN104651888A
Zinc-zinc nickel electroplating method of neodymium iron boron magnet
CN106835209A
Process of neodymium-iron-boron magnet composite electric galvanizing-zinc-nickel alloy
CN109056017A
Neodymium iron boron magnet surface anti-corrosion treatment method
CN110643989A
Method for electroplating zinc-nickel alloy, magnet, electroplating solution and purpose of potassium chloride
CN110983392A